A compact meander line uhf rfid antenna for passive tag applications - Bhaskar, S.; Singh, A.K. (Electromagnetics Academy, 2020)
In this article, a meander line dipole antenna for radio frequency identification (RFID) tag is presented. The loaded meander antenna has a simple meander line structure with a spiral inductor at the end for size miniaturization, a T-match structure, and an inductively coupled parasitic element for impedance matching with the tag IC. The antenna is designed to operate in North American UHF RFID frequency band of 915 MHz. The size of the proposed tag antenna is 50 mm × 12 mm and has good impedance matching with Alien Higgs IC chip of 13.5 − j111Ω at the desired frequency band. The proposed tag antenna provides omnidirectional radiation pattern with a maximum read range of 3.5 m at an effective isotropic radiated power of 4 W. Simulation results are in good agreement with measurement results. © 2020, Electromagnetics Academy. All rights reserved.